Showtime - Arthur, Robin 20. Jh; Lowdon, Richard ca. 20. Jh; Marshall, Claire (Forced Entertainment, 1996)
'Showtime' is a comical piece in which the concerns of adult life - especially death - are played out in a visual language drawn from children's picture books and pantomimes. Its concern is with the theatre itself - with the nature of our demands as spectators, with the construction of illusion as well as with the desire for order, sense and coherence in our lives
High quality multi-camera performance documentation